An analysis of warm-up strategies at a cross-country skiing national championship - Jones, T. W.; Govus, A. D.; Buskqvist, A.; Andersson, E. P.; McGawley, K. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To provide a descriptive analysis of the warm-up (WU) strategies employed by cross-country skiers prior to distance and sprint competitions at a national championship and to compare the skiers` planned and executed WUs prior to the respective competitions. Methods: Twenty-one national- and international-level skiers (11 women and 10 men) submitted WU plans prior to the distance and sprint competitions, and after the competitions, reported any deviations from the plans. Skiers used personal monitors to record heart rate (HR) during WU, races, and cooldown. Quantitative statistical analyses were conducted on WU durations, durations in HR-derived intensity zones, and WU loads. Qualitative analyses were conducted on skiers` WU plans and their reasons for deviating from the plans. Results: Skiers` planned WUs were similar in content and planned time in HR-derived intensity zones for both the distance and sprint competitions. However, 45% of the women and 20% of the men reported that their WU was not carried out as planned, with reasons detailed as being due to incorrect intensities and running out of time. WU activities including skiing across variable terrain, muscle-potentiating exercises, and heat-maintenance strategies were missing from the skiers` planned routines. Conclusions: Skiers favored a long, traditional WU approach for both the sprint and distance events, performing less high-intensity and more moderate-intensity exercise during their WUs than planned. In addition, elements likely relevant to successful performance in cross-country skiing were missing from WU plans.